Entre a bacia de barbeiro e a navalha da justiça literária: uma análise de O elmo de Mambrino de Lívio Xavier - Inocêncio, Matheus Coelho (2024)
This research focuses on the analysis of the work O elmo de Mambrino (1975) by Lívio Xavier (1900-1988), aiming to understand its critical approach, its relevance in Brazilian literary criticism, and its contributions to the literary historiography of the 20th century. The book compiles critical commentaries, reviews, and short essays that were published as newspaper articles between the 1930s and 1970s, during the height of what is known as "footnote criticism". In addition to his political activism, Xavier was deeply involved in literary criticism and production, translation, and editing, positioning himself within a network of intellectual sociability. This study seeks to identify recurring themes, influences, and Xavier’s contributions to literary criticism in Brazil. One of its objectives is to understand Xavier as a cultural mediator, who made literature accessible to a broad, non-specialized audience. Furthermore, it aims to analyze literature as a social field, shaped by agents competing for space and power relations. This work is structured into chapters that address the context of footnote literary criticism, an examination of Xavier’s criticism in relation to his peers, and the dialogues his texts establish with other intellectuals such as Mário de Andrade and Antonio Candido. The research also explores the history of the book and reading as tools to broaden interpretations of the work and understand its relationship with other texts and sociocultural contexts. It is expected that the research will provide a deeper understanding of Lívio Xavier’s contributions to Brazilian literary criticism and his importance in shaping 20th-century critical-literary practices. The comparative analysis of his texts will highlight the uniqueness of Xavier's work and his influence on the formation of a critical tradition in Brazil.